Spectromorphological Timbral Notation as a Tool for Malaysian Ethnomusicology - Abdullah, Mohd Hassan; Blackburn, Andrew S. (Malaysian Journal of Music, 2015)
Ethnomusicologists often face the problem of precisely and objectively describing the characteristics of a sound recorded in fieldwork activities. ln the absence of any other means, written explanations normally use metaphoric words to represent the timbral characteristics of a sound produced by ethnic musical instruments. But to what extent will the reader understand and perceive the sound based on the writer’s explanation? This study is part of a wider research project Spectromorphological Notation - Notating the unNotatable? Modelling a New System of Timbral and Performance Notation for Ethnomusicological, Musique-mixte and Electroacoustic Music Compositions. This articlewill explore some of the possibilities of using timbral visualisation in the recognition of the characteristics of Malaysian traditional musical instruments with a view of providing a more objective description of the sound of these instruments. Such analysis of Malay traditional instruments is new. As part of a wider cataloguing and analysis of this group of instruments, we focus on the timbre of one instrument in particular, the gedombak (goblet drum). We introduce an instrument recognition process from our solo recordings of a set of Malay traditional instruments, which in the examples provided, are yielding a high recognition rate. A large sound profile is used in order to encompass the different sound characteristics of each instrument and evaluate the generalisation abilities of the recognition process. Our approach is to then use understanding gained by this process to visualise the sound qualities preferred by an experienced and professional Wayang Kulit performer when selecting specific instruments for a given dramatic story or context.